2021
DOI: 10.3390/molecules26144239
|View full text |Cite
|
Sign up to set email alerts
|

Aspochalasin H1: A New Cyclic Aspochalasin from Hawaiian Plant-Associated Endophytic Fungus Aspergillus sp. FT1307

Abstract: Aspergillus is one of the most diverse genera, and it is chemically profound and known to produce many biologically active secondary metabolites. In the present study, a new aspochalasin H1 (1), together with nine known compounds (2–10), were isolated from a Hawaiian plant-associated endophytic fungus Aspergillus sp. FT1307. The structures were elucidated using nuclear magnetic resonance (NMR) (1H, 1H-1H COSY, HSQC, HMBC, ROESY and 1D NOE), high-resolution electrospray ionization mass spectroscopy (HRESIMS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…FT1307 associated with plant Heliotropium sp. Compounds 159-162 showed weak activity against Staphylococcus aureus ATCC12600, Bacillus subtilis ATCC6633 and MRSA ATCC43300 with MICs in the range of 40 to 80 µg/mL [84].…”
Section: Aspergillusmentioning
confidence: 99%
“…FT1307 associated with plant Heliotropium sp. Compounds 159-162 showed weak activity against Staphylococcus aureus ATCC12600, Bacillus subtilis ATCC6633 and MRSA ATCC43300 with MICs in the range of 40 to 80 µg/mL [84].…”
Section: Aspergillusmentioning
confidence: 99%
“…Our earlier studies have shown that 90 and 100% fractions contain similar, diverse metabolite patterns and biological activities compared to the 50% fraction. Hence, further studies focused on the combined 90 and 100% fractions (Wang et al ., 2020 a , 2020 b ; Yu et al ., 2020 ; Qader et al ., 2021 ; Zaman et al ., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability assay of small-scale extracts to prioritize strains for large-scale fermentation The small-scale extracts prepared from isolated fungal strains were tested for the lack of toxicity against one or other of three human cell lines: HT1080 (fibrosarcoma cell line), T46D (breast cancer cell line) and A2780S (ovarian cancer cell line). Nontoxic extracts produced by the respective fungal strains were prioritized for large-scale fermentation (Wang et al, 2020a;Qader et al, 2021;Zaman et al, 2021).…”
Section: Fermentation and Extractionmentioning
confidence: 99%
“…Structurally, cytochalasins have a highly substituted perhydroisoindol-1-one moiety, which is fused with a 9- to 15-membered macrocyclic ring. Many cytochalasins exhibit a wide range of biological activities, such as cytotoxic, antimicrobial, and phytotoxic properties [ 48 , 72 , 73 , 74 ]. Indole alkaloids are another group of compounds represented among plant endophytes.…”
Section: Chemical Diversity Of Bryendophyte Metabolitesmentioning
confidence: 99%